OF THE CONCEPTIONS OF MECHANISM OF MOTIVATSON OF CORPORATIVE MANAGEMENT - Давыдова, И. А. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
The article presents the results of retrace of the evolution of corporative management conceptions which reflect the positions of different schools of the economic science. Influence of these conceptions on quality of management of great modern organizations is considered.